DETERMINATION OF SUSTAINABLE BUSINESS FACTORS OF ISLAMIC BANKS IN INDONESIA - Siswanti, Indra (Accounting Department,, 2019)
The objective of the study is to test and analyze the influence of corporate intellectual capital and company size on sustainable business through financial performance as a mediating variable. The data used was secondary data of financial and annual reports for 2010-2018 period. The population of this study was 9 (nine) Islamic Banks, and the samples used were saturated sampling, thus the sample used was all the 9 (nine) Islamic Banks. The data processing method used is Partial Least Square (PLS). The results of the study found that intellectual capital has a significant effect on financial performance, company size has a significant effect on financial performance, where as intellectual capital has no effect on sustainable business. The study found that financial performance has a significant effect on sustainable business. Financial performance has a full mediating influence of intellectual capital on sustainable business, and financial performance has a partial mediating influence of company size on sustainable business. Keywords: Intellectual Capital, Company size, Financial Performance, and Sustainable Business